News sentiment and bank credit risk - Smales, Lee (Elsevier, 2016)
This article seeks to consider the relationship between the sentiment of newswire messages for a set of major international banks and changes in two important credit measures; the LIBOR-OIS spread and the CDS spread. There is a significant and negative relationship between news sentiment and changes in CDS spreads, which is consistent with ex-ante expectations that credit risk will decrease (increase) with positive (negative) news. This relationship is asymmetric with negative news inducing a stronger effect than positive news. There is also an apparent strengthening in this news sentiment/credit risk relationship during the crisis period. This coincides with a period when the number of news articles is highest, and the availability of news has a significant influence on CDS spreads. There is some evidence that whilst market determined credit measures (CDS spreads) respond to news releases, bank determined measures (LIBOR-OIS spreads) do not. Such results add to the discussion on whether banks correctly incorporate news into their own evaluation of credit risk. Understanding the behaviour of credit risk measures aids market participants, regulators, and central bankers in determining appropriate policy choices.